Glutaredoxin 1 Downregulation in the Substantia Nigra Leads to Dopaminergic Degeneration in Mice. Issue 10 (3rd July 2020) - Verma, Aditi; Ray, Ajit; Bapat, Deepti; Diwakar, Latha; Kommaddi, Reddy Peera; Schneider, Bernard L.; Hirsch, Etienne C.; Ravindranath, Vijayalakshmi
Abstract: Background: Parkinson's disease (PD) is characterized by a severe loss of the dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc). Perturbation of protein thiol redox homeostasis has been shown to play a role in the dysregulation of cell death and cell survival signaling pathways in these neurons. Glutaredoxin 1 (Grx1) is a thiol/disulfide oxidoreductase that catalyzes the deglutathionylation of proteins and is important for regulation of cellular protein thiol redox homeostasis. Objectives: We evaluated if the downregulation of Grx1 could lead to dopaminergic degeneration and PD‐relevant motor deficits in mice. Methods: Grx1 was downregulated unilaterally through viral vector‐mediated transduction of short hairpin RNA against Grx1 into the SNpc. Behavioral assessment was performed through rotarod and elevated body swing test. Stereological analysis of tyrosine hydroxylase–positive and Nissl‐positive neurons was carried out to evaluate neurodegeneration. Results: Downregulation of Grx1 resulted in contralateral bias of elevated body swing and reduced latency to fall off, accelerating rotarod. This was accompanied by a loss of tyrosine hydroxylase–positive neurons in the SNpc and their DA projections in the striatum. Furthermore, there was a loss Nissl‐positive neurons in the SNpc, indicating cell death. This was selective to the SNpc neurons because DA neurons in the ventral tegmental area were unaffected akin to that seen in human PD. Furthermore, Grx1 mRNA expression was substantially decreased in the SNpc from PD patients. Conclusions: Our study indicates that Grx1 is critical for the survival of SNpc DA neurons and that it is downregulated in human PD. © 2020 International Parkinson and Movement Disorder Society